High Involvement Management and its role in Achievement of Job Satisfaction: Applied Study in College of Administration & Economics- Diyala University - Jumaah, Mahmood Hasan (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to test the relationship of linkage and the effect between the hig involvement management and job satisfaction. The problem of the research is to pose the role of high involvement management in achievement job satisfaction in College of Administration & Economics- Diyala University. A questionnaire was used in data collection depending on the distribution of (58) questionnaire to the research sample. Data were analyzed using (SPSS) program. Using a number of statistical tools to test the research hypothesis. The research comes out with a set of conclusions; one of the most important remarks is that there is a linkage and impact relation between high involvement management, its variables (functional consolidation, training, incentive, knowledge possession) and job satisfaction as a whole. The research comes out with many suitable recommendations.